A Real-Life Turkish Experience of Ruxolitinib in Polycythemia Vera - Serin, Istemi; Dogu, Mehmet Hilmi; Ekinci, Omer; Cagliyan, Gulsum Akgun; Basturk, Abdulkadir; Aras, Merih Reis; Altuntas, Fevzi (Galenos Publ House, 2023)
Introduction: Ruxolitinib is a small -molecule inhibitor of the JAK1/2 pathway. This study aimed to reveal the results and side-effect profile of the use of ruxolitinib as a treatment option in polycythemia vera (PV). Methods: A total of 34 patients with PV from 18 different centers were included in the study. The evaluation of the response under treatment with ruxolitinib was determined as a reduction in spleen volume (splenomegaly size: >= 35%) by imaging and control of hematocrit levels (<= 45%) compared to baseline. Results: While the number of patients in which a reduction in spleen volume and hematocrit control was achieved was 19 (55.9%) at 3 months of treatment, it was 21 (61.8%) at 6 months. Additionally, while the number of side effects was negatively correlated with the reduction in spleen volume (Spearman's rho: -0.365, p=0.034), a decrease in the hematocrit level was positively correlated (Spearman's rho: 0.75, p=0.029). Those without a reduction in spleen volume experienced more constipation (chi-square: 5.988, Fisher's exact test: p=0.033). Conclusion: This study shed light on the use of ruxolitinib in PV and the importance of splenomegaly on studies planned with larger patient groups.
Keywords: Polycythemia vera; ruxolitinib; real-life data; response; side effect